The origin and development of the Pleistocene LSA in Northwest Africa: A case study from Grotte des Pigeons (Taforalt), Morocco - Hogue, J; Joshua Hogue (2014)
This thesis examines variation within the microlith industries of the Later Stone Age (LSA) of Northwest Africa, around the time of the Last Glacial Maximum (LGM) until the onset of the Holocene, between ∼25 - 11.5 ka. The traditionally held view is that whilst there is variation amongst the lithic assemblages, this can all be accommodated by a single definable industry, known as the Iberomaurusian. This thesis indicates an alternative scenario. Based on the typo-technological analysis of 16,689 lithic artefacts recovered from recent excavations at the site of Grotte des Pigeons (Taforalt, Morocco) and the re-analysis of published data using the multivariate statistical approach of correspondence analysis (CA), this thesis shows that there was much greater variation than previously proposed within the Pleistocene LSA. This thesis indicates that the LSA industries can be sub-divided into four chronologically distinct variants, an Initial LSA time-coincident with the first appearance of microlithic technology from ∼25 ka and lasting up until Heinrich event 2, a succeeding Early LSA at ∼22 ka that continued until Heinrich event 1, a Middle LSA marking a shift in technologies around this event at ∼16 ka, and an Upper LSA occurring with the climatic amelioration of the Bølling-Allørod at ∼14.5 ka. The proposed chronological model provides a new framework for categorising variation within the LSA, which is a necessary pre-requisite for potential future research addressing wider anthropological and archaeological issues, such as reasons for shifts in subsistence and settlement.